Active Vibration Isolation Devices with Inertial Servo Actuators - Melik-Shakhnazarov, V. A.; Strelov, V. I.; Sofiyanchuk, D. V.; Tregubenko, A. A. (Cosmic research, 2018)
The use of active vibration isolation devices (AVIDs) in aerospace engineering is subject to the following restrictions. First, the volume for installing additional devices is always limited in instrument racks and compartments. Secondly, in many cases, it is impossible to add supports for servo actuators for fundamental or design considerations. In the paper, it has been shown that this problem can be solved if the inertial servo actuators are used in AVIDs instead of reference actuators. A transfer function has been theoretically calculated for an AVID controlled by inertial actuators. It has been shown that the volume of a six-mode single-housing AVID with inertial actuators can be 2–2.5 times smaller than that of devices with support actuators.